Molecular diagnosis of kidney transplant rejection - Morath, Christian; Zeier, Martin (Nature reviews. Nephrology, 2014)
Acute or chronic antibody-mediated rejection (ABMR) of kidney allografts is currently diagnosed by the presence of donor-specific alloantibodies and distinct pathological findings in biopsy samples. A new study highlights the potential of molecular diagnostics incorporated into standard criteria for acute ABMR to help identify patients at risk of graft loss.
Gesehen am 08.09.2020